Implementasi SILONDO dalam Kerangka New Public Service pada Layanan Administrasi Kependudukan di Depok - Marsheila, Fitri; Budaya, Cikal Adelaide; Atthar, Mohammad Noufal; Fattah, Sahalani Mawla; ., Ridwan (Peneliti.net, 2026)
This study examines the implementation of SILONDO (Depok Civil Registry Online Service System) through the perspective of New Public Service (NPS), which emphasizes citizen participation, democracy, and humane service. Using a qualitative-descriptive approach, this study analyzes the extent to which the seven principles of NPS are reflected in the digital services of the Depok City Civil Registry Office. The results indicate that while SILONDO introduces technology-based innovations and inclusive programs such as on-demand services, its implementation still faces challenges such as low responsiveness of staff, weak complaint mechanisms, and limited outreach. Accountability is more focused on numerical achievements than on citizen experiences. SILONDO is a progressive innovation but has not fully embodied the values of NPS. Strengthening participatory aspects and democratic accountability is necessary to make digital public services more inclusive and equitable.